Improving Guidance and Counseling Services for Effective Service Delivery in Nigerian Secondary Schools - Suleiman, Yusuf; Olanrewaju, Muraina Kamilu; Suleiman, Jamiu Mahmood (Departemen Psikologi Pendidikan dan Bimbingan FIP Universitas Pendidikan Indonesia, 2019)
Guidance and counselling is a service that all human beings need at one point of their life. There is no human being that has never got a problem at one point or another. Guidance counselling is a noble profession whose importance in the educational system of Nigeria is becoming increasingly recognized by the country’s educational planners and policy makers. Ideally a well-trained school counsellor should be available in each institution in the federation to deal with various aspects of students’ problems and this presupposes the establishment of school guidance and counselling from the primary up to the tertiary levels. The essentials services expected of guidance counsellor in schools was highlighted and the means through which guidance programmes could be enhanced for effective service delivery in Nigerian secondary schools were expatiated. The process involves putting the prevailing situation in proper perspective by identifying the challenges and counselling is a problems solver. The role of the counsellor is to coordinate all the school guidance personnel in order to achieve effective guidance and by extension, the school objectives. The paper however, recommended that guidance service should be integrated into the primary school curriculum and be taught as a class subject and that administration of each institution provides critical leadership and conducive work environment to accommodate the kind of flexible work schedule and organizing regular workshops, seminars and conferences for stakeholders in guidance and counselling.